Global City Competitiveness: Gendered Labor Dynamics and Women’s Economic Participation in Jakarta, Indonesia - Widyaningrum, Novi; Sekarjati, Citra (Policy & Governance Review, 2026)
Globalization and digital economic transformation have intensified competition among cities to strengthen their positions in global economic networks. While glob- al city scholars have traditionally emphasized advanced producer services, finance, and highly skilled labor as the primary drivers of urban competitiveness, less atten- tion has been given to the gendered dynamics of urban labor markets. This study examines how women’s economic participation contributes to urban competitive- ness in Jakarta, a rapidly transforming metropolitan region experiencing structural adjustments as Indonesia’s national capital. A qualitative case study approach was employed, drawing on semi-structured interviews with 18 informants representing government agencies, financial institutions, civil society organizations, and women entrepreneurs, complemented by secondary data from policy documents and official statistics. The findings indicate that women play a significant role in sustaining Jakar- ta’s urban economy through microenterprises, digital entrepreneurship, and localized production networks that support household income and community-level employ- ment. However, women’s economic participation remains constrained by structural barriers, including limited digital and financial literacy, household economic vulner- ability, gender segmentation within digital markets, and fragmented policy support for microenterprise development. These findings suggest that urban competitiveness cannot be understood solely through high-value global economic sectors; decentral- ized entrepreneurial networks that sustain local economic resilience must also be con- sidered. Therefore, this study argues that gender-inclusive economic participation constitutes a structural component of sustainable urban competitiveness in emerging globalizing cities.